2010
DOI: 10.1039/c0sm00367k
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of alkanes from the vapour phase on water drops measured by drop profile analysis tensiometry

Abstract: In this paper it is demonstrated that short chain alkanes (pentane, hexane, heptane, octane) can be adsorbed from a saturated vapour phase at the water-air interface. Measurements with the drop profile analysis tensiometry demonstrate that this molecular adsorption transfers into a condensation leading to a thin alkane film at the drop surface. At sufficient amounts, i.e. after such a film has reached a respective thickness, the condensed liquid starts to drain and an oil lens of alkane is formed at the water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 18 publications
(17 reference statements)
1
37
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] In all these studies, the adsorption of alkane was shown to result in a significant decrease of the surface tension. [1][2][3][4][5][6][7][8][9] In all these studies, the adsorption of alkane was shown to result in a significant decrease of the surface tension.…”
Section: Doi: 101002/admi201600031mentioning
confidence: 96%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9] In all these studies, the adsorption of alkane was shown to result in a significant decrease of the surface tension. [1][2][3][4][5][6][7][8][9] In all these studies, the adsorption of alkane was shown to result in a significant decrease of the surface tension.…”
Section: Doi: 101002/admi201600031mentioning
confidence: 96%
“…The adsorption of alkane vapor from the gas phase at the surface of pure water drops was extensively studied for alkanes of various chain lengths and for different partial pressures of alkanes in the gas phase. [1][2][3][4][5][6][7][8][9] In all these studies, the adsorption of alkane was shown to result in a significant decrease of the surface tension. In ref.…”
Section: Doi: 101002/admi201600031mentioning
confidence: 96%
“…Various experimental and theoretical studies of adsorption of alkanes from the gas phase on a water surface were previously reported [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The thickness of such adsorbed alkane layers was determined with optical methods being maximum up to 4-5 nm [6].…”
Section: Introductionmentioning
confidence: 99%
“…During last years, a large pool of experimental data was collected, and theoretical models were developed for the adsorption of alkanes from the gas phase on the surface of a water drop [7][8][9][10][11][12][13][14][15][16][17]. It was shown, for instance, that the adsorption of alkanes from the gas phase results in a significant decrease of the surface tension of water or aqueous protein (surfactant) solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation